Mentorship in endocrinology training: a cross-sectional study of the United States and EuropeResearch in context - David Toro-Tobon; Heather Billings; Anina F. Peersen; Elizabeth J. Atkinson; Antoan S. Sojat; Ljiljana V. Marina; Irina Bancos (EClinicalMedicine)
Summary: Background: Mentorship is crucial for developing both scientific and professional competencies in medical training, yet its role in endocrinology training remains underexplored. We aimed to assess the prevalence of mentorship in endocrinology trainees, analyse demographic and training programme factors, and evaluate the impact of mentor characteristics on trainee outcomes. Methods: We conducted a cross-sectional study of endocrinology trainees in the United States and Europe (23 countries) between June 2023 to January 2024. Participants were recruited via professional societies, email lists, and social media. Those who had completed more than 7 years of training post-medical school or had missing data on duration of training were excluded. A structured online questionnaire was developed using validated mentorship competency tools and adapted for regional nuances to collect data on demographics, mentorship experiences, academic productivity, and well-being. The primary outcome assessed the prevalence of mentorship; secondary outcomes evaluated the associations between mentor characteristics and self-reported academic productivity, satisfaction within the mentorship relationship, and levels of burnout and stress. Univariable and multivariable logistic regression analyses were conducted. Findings: Between June 10, 2023, and January 1, 2024, 250 respondents (154 from the U.S. and 96 from Europe; 70.0% women, 64.4% White), 75.8% reported having a mentor. Significant regional differences emerged: U.S. trainees predominantly self-selected their mentors (69.7% vs. 23.1% in Europe) and reported less frequent interactions (monthly or less vs. more than weekly in Europe). Univariable analyses revealed that attributes such as active listening, inspirational guidance, and personalised career support were strongly linked to enhanced academic productivity, higher training satisfaction, and reduced burnout. In multivariable models, inspirational guidance was a significant predictor of academic productivity among U.S. trainees (94.4% vs. 35.3%, OR: 54.72, 95% CI: 4.7–2255.9), while in Europe, mentors facilitating strategic goal-meeting was associated with decreased burnout (77.8% vs. 40.0%, OR: 5.49, 95% CI: 1.1–33.7) and inspirational guidance with markedly improved mentorship satisfaction (90.7% vs. 28.6%, OR: 51.86, 95% CI: 2.2–1177.2). Interpretation: Though the design precludes causal inference, these findings underscore the universal benefits of mentorship in endocrinology training and highlight that targeted mentor competencies are key drivers of trainee success. Tailoring mentorship frameworks to regional training contexts may optimise academic productivity, training satisfaction, and overall well-being. Future longitudinal and qualitative studies are needed to clarify causal pathways and evaluate the effectiveness of tailored mentorship interventions. Funding: The National Center for Advancing Translational Sciences (NCATS).